Technical note: A simplified PCR-based assay for the characterization of two prolactin variants that affect milk traits in sheep breeds - Orford, Michael R.; Tzamaloukas, Ouranios; Miltiadou, Despoina; Papachristoforou, Christakis (My University, 2010)
In the present study, a rapid and cost-effective PCR-based assay was developed for the genetic identification of 2 different variants within intron 2 of the prolactin gene. This polymorphism has previously been associated with milk traits in some ovine breeds and was recently proposed as a potential marker for future breeding schemes in dairy sheep. Until now, 2 alleles (A and B) have been identified by PCR-RFLP that included HaeIII digestion of a 2.5-kb PCR fragment. By partial sequencing of the prolactin gene intron 2, it was found that the B variant results from a 23-bp deletion of the A variant of the prolactin gene and not from an extra HaeIII digestion site, as had been reported. This finding assisted the design of new primers for analysis of prolactin intron 2 variants based on the size of an easily amplified short PCR product, thereby avoiding the need and cost for additional digestions. The method was validated by genotyping 80 animals from 2 breeds and showed 100% sensitivity and specificity compared with the PCR-RFLP assay. The established simplified PCR assay was then successfully used to genotype 356 Chios sheep.
Keywords: Genotyping; Marker assisted selection; Polymerase chain reaction–restriction fragment length polymorphism; Prolactin